2020
DOI: 10.1007/s00415-020-10106-z
|View full text |Cite
|
Sign up to set email alerts
|

Presentation outside office hours does not negatively influence treatment times for reperfusion therapy for acute ischemic stroke

Abstract: Background Treatment outside office hours has been associated with increased workflow times for intravenous thrombolysis (IVT) in acute ischemic stroke (AIS). Limited data suggest that this "off-hours effect" also exists for endovascular treatment (EVT). We investigated this phenomenon in a well-organized acute stroke care region in the Netherlands. Methods Retrospective, observational cohort study of consecutive patients with AIS who received reperfusion therapy in the Greater Amsterdam Area, consisting of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(22 reference statements)
2
5
1
Order By: Relevance
“…Similar to previous multicenter studies 16,[24][25][26][27] , this study did not reveal a difference in the prognosis or rate of complications between the two groups. Benali et al observed a significantly higher rate of good functional outcomes among inpatients admitted at night (51% vs. 35%, P = 0.05) 28 , but another study found a higher mortality rate among patients admitted at night for EVT 29 , which may be due to the heterogeneity of the stroke center process and sample size.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous multicenter studies 16,[24][25][26][27] , this study did not reveal a difference in the prognosis or rate of complications between the two groups. Benali et al observed a significantly higher rate of good functional outcomes among inpatients admitted at night (51% vs. 35%, P = 0.05) 28 , but another study found a higher mortality rate among patients admitted at night for EVT 29 , which may be due to the heterogeneity of the stroke center process and sample size.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous multicenter studies (16,(24)(25)(26)(27), this study did not reveal a difference in the prognosis or rate of complications between the two groups. Benali et al observed a significantly increased rate of good functional outcomes among inpatients admitted at night (51 vs. 35%, P = 0.05) (28), but another study found a higher mortality rate among patients admitted at night for EVT (29), which may be due to heterogeneity in stroke center processes and sample sizes.…”
Section: Discussionsupporting
confidence: 90%
“…One of the reasons might be the variation of DNT. One study in the Netherlands showed that early care helped reduce DNT time and decreased patients' NIHSS scores [ 17 ], and another study in the Netherlands showed that overwork affected DNT time [ 18 ]. Given that there was no difference in the time between onset and admission of patients in this study, the effect of DNT on outcomes may have been magnified, leading to worse outcomes in 2020 than in 2019.…”
Section: Discussionmentioning
confidence: 99%